An outline of clinical decision making for physiotherapists - Abdullahi, Auwal (Cambridge Scholars Publisher, 2019)
This volume takes therapists and other health professionals on a journey of self-discovery, wherein they will find guides on how to hone their clinical skills in making clinical decisions. Additionally, it will help the therapist arm themselves with the necessary skills to practice within the realm of ethics.
Keywords: Physical therapy -- Decision making.; Physical therapists -- Professional ethics.; Decision making.; Physical therapy.; Decision Making; Physical Therapy Modalities; Physiothérapie -- Prise de décision.; Physiothérapeutes -- Déontologie.; Prise de décision.; Physiothérapie.; decision making.; Physical therapy; Decision making; Physical therapists -- Professional ethics; Physical therapy -- Decision making